Analysis of Energy Harvesting Techniques and Uses for Microelectronics (International Journal of Innovative Research in Computer Science & Technology, 2022)
Increasingly advanced equipment may  now be smaller and use less power thanks to technological  advancements. These deteriorate but also power ushers in  new wearable technology paradigms, with a slew of  embedded systems cooperating or at the very least having  better communication capabilities. Smart watches and  remote monitoring are examples among those new  paradigms. These devices are generally powered by  batteries. However, batteries have a number of drawbacks,  including the need to renew or refresh them on a regular  basis, as well as their considerable size and weight when  compared to current technological products. Collecting  (harvesting) energies first from ambient to either recharge  a battery or directly charge the digital circuit is one way to  get over this power limits. This article presents numerous  approaches to design a space is provided network and data  on the sort of energies available.
Keywords: Electronics; Energy Harvesting; Technology; Wearable Devices; Wireless Sensor Networks